FEATURES OF VITAMIN-D METABOLISM IN PATIENTS WITH DIABETIC NEPHROPATHY - Ismoilov, Jamshid Abduraimovich; Egamberdiyeva, Yulduz Komiljon kizi; Mahmamuradova, Nargiza Negmatullayevna; Daminov , Abdurasul Takhirovich (Educational Research in Universal Sciences, 2024)
Diabetic nephropathy (DN) is a specific kidney damage in diabetes mellitus (DM), caused by the influence of hemodynamic and metabolic factors. It is in the kidneys that an important stage of vitamin D metabolism occurs—1α-hydroxylation, which results in the formation of its main biologically active form. A decrease in the number of functioning nephrons in DN leads to disruption of vitamin D metabolism, contributing to the development of a number of complications. In this review, we dwell in detail on both the normal metabolism of vitamin D and the peculiarities of vitamin D metabolism in chronic kidney disease (CKD). DN is the most common cause of CKD and, as a consequence, kidney transplantation, as well as one of the leading causes of cardiovascular morbidity and mortality in patients with diabetes. Mineral and bone disorders due to CKD, caused by abnormal vitamin D metabolism, are also independent factors of high mortality among patients with DN. The final part of our review briefly highlights modern approaches to vitamin D therapy in CKD, and in particular DN. It is worth noting that, despite the growing number of patients with DN, there is currently no consensus on the use of vitamin D as a therapeutic agent for this pathology.